Giant dielectric ceramic with low dielectric loss and preparation method thereof
By applying a large current oscillation pressure during the sintering process, the problem of high dielectric loss of giant dielectric ceramic materials is solved, and a material preparation with high dielectric constant and low dielectric loss is achieved.
Patent Information
- Application Number
- CN202411486290.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing giant dielectric ceramic materials have high dielectric loss problems during the sintering process, which limits the development of the electronic materials industry.
The high-current oscillation pressure sintering process is adopted to apply oscillation pressure and high current during the sintering process, and dielectric loss is reduced by extruding the crystal grains and polarized electric domains.
The preparation of perovskite giant dielectric ceramic materials with high dielectric constant and low dielectric loss has been achieved, and the performance of the materials has been improved.
Smart Images

Figure HDA0005098790580000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of giant dielectric ceramics, and in particular to a low dielectric loss giant dielectric ceramic and a preparation method thereof. Background Art
[0002] Giant dielectric ceramics refer to ceramics with a relative dielectric constant of 10 4 The above dielectric ceramic materials are excellent new capacitor materials. With the increasing popularity of new energy vehicles and new power grids, the demand for giant dielectric ceramic materials will continue to increase. The most common ferroelectric giant dielectric ceramics are perovskite materials. The first perovskite giant dielectric ceramic materials put into industrial production are Pb-based lead zirconate titanate (PbZr x Ti 1-x O3) and barium titanate (Ba x Sr 1-x TiO3) materials are the main ones.
[0003] At present, the preparation methods of several common perovskite giant dielectric ceramics such as BaTiO3, PbTiO3, SrTiO3, etc. can be divided into solid phase sintering, hot pressing sintering (HP), hot isostatic pressing sintering (HIP), flash sintering (FS), spark plasma sintering (SPS), etc. Each method has its advantages and disadvantages and applicability. The existing literature and patents related to the field of giant dielectric ceramic preparation technology mainly include CN114262223A, CN 115321976A and CN103214237B. Among them, patent CN114262223A is about the flash sintering method for preparing TiO2-based giant dielectric ceramics. Compared with conventional sintering, the sintering time and sintering temperature are significantly reduced, and giant dielectric ceramics with smaller grain size and more uniform structure can be obtained. Although this method improves the dielectric constant, it still has the problem of high dielectric loss; patent CN115321976A adopts a solid phase sintering process, that is, Nd2O3 and Nb2O5 are added on the basis of preparing CCTO giant dielectric ceramic materials, and ceramic materials with giant dielectric constant and low dielectric loss are obtained through solid phase sintering, but the grain size cannot be guaranteed, which affects the mechanical properties of the product; patent CN103214237B uses self-propagating high temperature rapid pressure technology to sinter barium titanate ceramics. Although the dielectric constant is improved, its dielectric loss is relatively high, and the dielectric constant changes greatly with temperature.
[0004] Although the giant dielectric ceramic samples prepared by the existing sintering technology have improved the dielectric constant, they are also accompanied by high dielectric losses. This phenomenon has greatly restricted the development of the electronic materials industry. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing giant dielectric ceramics with high dielectric constant and low dielectric loss.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing low dielectric loss giant dielectric ceramics comprises the following steps:
[0008] (1) ball milling: placing the perovskite giant dielectric ceramic powder, the dispersion medium and the ball milling medium into a ball milling jar, and ball milling the perovskite giant dielectric ceramic powder at a first ball milling speed and a first ball milling time to obtain a ball milled and uniformly mixed slurry;
[0009] (2) Granulation: adding polyvinyl alcohol aqueous solution to the slurry, ball milling the slurry for a second time at a second ball milling speed and a second ball milling time, drying the slurry, ball milling the slurry for a third time, and sieving the slurry to obtain a crushed powder;
[0010] (3) Aging: Deionized water is added to the crushed powder to humidify it so that the water and the powder are evenly mixed, and then aging is started to obtain a mixed powder;
[0011] (4) Dry pressing: using a mold and a press, at a first pressure, keeping warm for a first time, the mixed powder is pressed into a sheet of ceramic with a certain thickness;
[0012] (5) Cold isostatic pressing: cold isostatic pressing is performed on the pressed ceramic disc using a second pressure and a second heat preservation time, and the disc is placed in the air to stand and then dried;
[0013] (6) Sintering: The cold isostatically pressed ceramic sheets are moved into an oscillating sintering furnace and a high current oscillating pressure sintering process is used. Oscillating pressure and high current are applied in different sintering stages. After cooling, a perovskite-type giant dielectric ceramic with a high dielectric constant and low dielectric loss is obtained.
[0014] The perovskite-based giant dielectric ceramic powder includes BaTiO3 powder, PbTiO3 powder or SrTiO3; the purity of the perovskite-based giant dielectric ceramic powder is ≥99.9%.
[0015] The dispersion medium is deionized water, the ball milling medium is a zirconia grinding ball with an addition ratio of φ10:φ5=(8-4):1; the ball milling jar is a nylon material or a zirconia material of 250nm-500ml; the ball mill is a vertical planetary ball mill, the first ball milling speed is 300rpm-400rpm, and the first ball milling time is 2-4h; the weight ratio of the perovskite giant dielectric ceramic powder to the ball milling medium is 1:(2-5); the weight ratio of the perovskite giant dielectric ceramic powder to deionized water is 1:(2-3).
[0016] The concentration of the polyvinyl alcohol aqueous solution is 3wt.%-5wt.%, the mass percentage of the added polyvinyl alcohol aqueous solution to the slurry is 5wt.%-8wt.%, the second ball milling speed is 200-250rpm, and the second ball milling time is 1-2h.
[0017] Furthermore, the slurry after the second ball milling is passed through a 20-80 mesh sieve, then moved into an oven and dried at 60°C-100°C for 24h-48h. The dried powder is poured into a nylon jar and ball milled for the third time at a ball milling speed of 60rpm-100rpm and a ball milling time of 0.5h-1h according to the ratio of zirconia grinding balls 500g=Φ20(75g)+Φ10(390g)+Φ5(35g). The crushed powder is then passed through a 20-100 mesh sieve and put into a ziplock bag.
[0018] The aging includes spraying deionized water into the crushed and sieved powder for humidification at a ratio of 1-3wt.% of deionized water to the crushed powder, repeatedly inverting and flipping the ziplock bag after spraying, the number of inversions and flippings is not less than 20 times, so that the water can be evenly mixed with the powder, and then aging for not less than 24 hours.
[0019] The first pressure is 60-75 MPa, and the first insulation time is 0-1 min; the second pressure is 200-250 MPa, and the second insulation time is 3-7 min; the wafer is placed in the air for 50-90 min, and then placed in a 60°C-100°C oven for drying.
[0020] The sintering stage includes:
[0021] Heating to 200°C at a heating rate of 1-5°C / min;
[0022] Raise the temperature from 200°C to 1200°C at a rate of 0.5-3.5°C / min;
[0023] The temperature was raised from 1200℃ to T at a rate of 0.2-1℃ / min. max , and at T max Keep at ℃ for 6-10h;
[0024] At a rate of 0.5-3.5℃ / min, the temperature max Cool down to 1100℃.
[0025] The high current oscillating pressure sintering process comprises the following steps:
[0026] The temperature was raised to 200°C at a rate of 1-5°C / min, an oscillating pressure of 10-30MPa was applied, and a current of (0.5-1)×10 3 A;
[0027] The temperature was raised from 200°C to 1200°C at a rate of 0.5-3.5°C / min, an oscillating pressure of 30-60MPa was applied, and a current of (1-2)×10 3 A;
[0028] The temperature is raised from 1200°C to T at a rate of 0.2-1°C / min. max , and at T max Keep at ℃ for 6-10h, apply oscillation pressure 40-60MPa, and pass current (2-4)×10 3 A;
[0029] The rate of 0.5-3.5°C / min is increased from T max Cool down to 1100°C, without applying oscillating pressure or passing current;
[0030] The T max It is 1300℃-1500℃.
[0031] The invention also provides a low dielectric loss giant dielectric ceramic, which is prepared according to the preparation method.
[0032] By means of the above technical solution, the present invention has at least the following advantages:
[0033] The present invention aims at the problems existing in the existing methods, adopts a solid phase reaction method, and uses a high-temperature and high-pressure oscillating sintering furnace. The reaction is simple, easy to operate, simple in process and low in cost. The present invention uses a large current oscillating pressure sintering process, applies oscillating pressure and large current in different sintering stages, and due to the influence of the oscillating pressure, the ceramic body is continuously squeezed during the growth of grains, the grains become smaller, and the domain walls increase. Under the action of the large current, the electric domains show an oriented polarization phenomenon, and when the large current is removed, the body can still maintain a relatively high residual polarization, and finally a perovskite-type giant dielectric ceramic with a high dielectric constant and low dielectric loss can be obtained.
[0034] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram comparing the high temperature and high pressure oscillation sintering curve provided by an embodiment of the present invention and the conventional sintering curve. DETAILED DESCRIPTION
[0036] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0037] like Figure 1 As shown, it is a comparison diagram of the conventional sintering curve and the high temperature and high pressure oscillation sintering curve. The first curve 1 is the conventional sintering curve, the second curve 2 is the high temperature and high pressure oscillation sintering curve, and the third curve 3 is the oscillation pressure. Figure 1 From the comparison between the first curve 1 and the second curve 2 + the third curve 3 in the figure, it can be seen that the dielectric loss of the giant dielectric ceramic obtained by the conventional sintering process of the first curve 1 is relatively large; while in the high-temperature and high-pressure oscillating sintering process of the second curve 2 + the third curve 3, oscillating pressure and a large current are applied during the heating process, that is, during the growth of the ceramic body grains, they are continuously squeezed, the grains become smaller, and the domain walls increase; under the action of the large current, the electric domains show an oriented polarization phenomenon, and when the large current is removed, the body can still maintain a high residual polarization, and a giant dielectric ceramic with a smaller grain size and lower dielectric loss can be obtained at the same time.
[0038] The present invention will be further described below by means of specific embodiments:
[0039] Each embodiment of the present invention adopts a planetary ball mill. In order to have the same load at symmetrical positions and prevent the planetary ball mill from being eccentric and damaging the equipment, two ball milling jars are arranged at symmetrical positions of the planetary ball mill, and the same material is added to each ball milling jar.
[0040] Example 1
[0041] (1) Ingredients: 50 g of BaTiO3 powder with a purity of 99.9%, 100 g of deionized water, and 150 g of zirconium oxide grinding balls (Φ10 (100 g) + Φ5 (25 g)) were loaded into a Φ250 ml zirconium oxide ball mill of a planetary ball mill. The same amount of BaTiO3 powder, deionized water, and zirconium oxide grinding balls were loaded into another Φ250 ml zirconium oxide ball mill at a symmetrical position of the planetary ball mill.
[0042] (2) Ball milling: Use a planetary ball mill with a rotation speed of 300 rpm to ball mill the BaTiO3 powder for 2 h to obtain a uniformly mixed slurry;
[0043] (3) Granulation: Add 5 wt.% polyvinyl alcohol aqueous solution to the slurry, the addition amount is 5 wt.%, and the planetary ball mill is 250 rpm. After 1 hour, the obtained slurry is passed through a 20-mesh screen. In order to filter the slurry and separate the grinding balls, the filtered slurry is poured into a plastic basin, covered with newspaper, and moved into an oven to dry at 60°C for 24 hours. The dried powder is poured into a nylon jar with an outer specification of Φ124×15, and the zirconia grinding ball ratio is 500g=Φ20 (75g) + Φ10 (390g) + Φ5 (35g). The powder is crushed again by ball milling at a ball mill speed of 60 rpm and a ball milling time of 0.5h. The crushed powder is passed through a 20-mesh screen and then put into a ziplock bag;
[0044] (4) Aging: Deionized water is added to the crushed and sieved BaTiO3 powder for humidification. The amount of deionized water added is 2 wt.% of the crushed and sieved BaTiO3 powder. The humidification process adopts a spraying process. After spraying, the self-sealing bag is repeatedly inverted and flipped 28 times to ensure that the water can be evenly mixed with the powder. Aging begins. The aging time is 25 hours;
[0045] (5) Dry pressing: Using a φ50 mold, the press pressure is 75 MPa, the heat preservation time is 0 min, and the mixed powder is pressed into a disc with a thickness of 5 mm;
[0046] (6) Cold isostatic pressing: The pressed discs were subjected to cold isostatic pressing at a pressure of 230 MPa and kept warm for 5 min to further improve the density of the green body. The discs were placed in air for 1 h and then dried in an oven at 60 °C to obtain BaTiO3 green body.
[0047] (7) Sintering: The BaTiO3 green body was sintered in a high temperature and high pressure oscillating sintering furnace. The temperature was raised to 200°C at a heating rate of 1°C / min, an oscillating pressure of 10 MPa was applied, and a current of 0.5×10 3 A; the temperature was raised from 200°C to 1200°C at a rate of 0.5°C / min, an oscillating pressure of 40 MPa was applied, and a current of 1.5×10 3 A; the temperature was raised from 1200℃ to 1500℃ at a rate of 1℃ / min and maintained at 1500℃ for 8h. 3×10 3A current, during the insulation period, the oscillation pressure is reduced from 40MPa to 30MPa in 1h of the 0-1h, the oscillation pressure is maintained at 30MPa in 2h of the 1-3h, the oscillation pressure is increased from 30MPa to 40MPa in 1h of the 3-4h, the oscillation pressure is reduced from 40MPa to 30MPa in 1h of the 4-5h, the oscillation pressure is maintained at 30MPa in 1h of the 5-6h, and the oscillation pressure is increased from 30MPa to 40MPa in 2h of the 6-8h; finally, the temperature is reduced from 1500℃ to 1100℃ at a rate of 2℃ / min, no oscillation pressure is applied, and no current is passed. Finally, a BaTiO3 giant dielectric ceramic material with a room temperature dielectric constant of 26826@1kHz and a dielectric loss of 0.017@1kHz is obtained.
[0048] Example 2
[0049] (1) Ingredients: 100 g of SrTiO3 powder with a purity of 99.9%, 240 g of deionized water, and 252 g of zirconium oxide grinding balls = Φ10 (216 g) + Φ5 (36 g), respectively, are loaded into two φ500 ml nylon grinding jars symmetrically located in a planetary ball mill;
[0050] (2) Ball milling: The planetary ball mill was set to a speed of 300 rpm, and the SrTiO3 powder was ball milled for 3 h to obtain a uniformly mixed slurry;
[0051] (3) Granulation: Add 3 wt.% polyvinyl alcohol aqueous solution to the slurry, the addition amount is 8 wt.% of the slurry, and the planetary ball mill is 200 rpm. After 2 hours, the obtained slurry is passed through an 80-mesh screen, poured into a plastic drying basin, covered with newspaper, moved into an oven, and dried at 100°C for 30 hours. The dried powder is poured into a nylon jar with an outer specification of Φ124×150, and the zirconia grinding ball ratio is 500g=Φ20(75g)+Φ10(390g)+Φ5(35g). The powder is crushed again by ball milling at a ball mill speed of 100 rpm and a ball milling time of 1 hour. The crushed powder is passed through a 100-mesh screen and placed in a ziplock bag;
[0052] (4) Aging: Deionized water is added to the crushed and sieved SrTiO3 powder for humidification. The amount of deionized water added is 1wt.% of the crushed and sieved SrTiO3 powder. The humidification process adopts a spraying process. After spraying, the self-sealing bag is repeatedly inverted and flipped 20 times to ensure that the water can be evenly mixed with the powder. Aging begins, and the aging time is 30 hours.
[0053] (5) Dry pressing: A 50×50 mm mold was used, the press pressure was 60 MPa, the holding time was 1 min, and the mixed powder was pressed into a square sheet with a thickness of 5 mm;
[0054] (6) Cold isostatic pressing: The pressed discs were subjected to cold isostatic pressing at a pressure of 250 MPa and kept warm for 3 min to further improve the density of the green body. The discs were placed in air for 50 min and then dried in an oven at 80°C to obtain SrTiO3 green bodies.
[0055] (7) Sintering: The SrTiO3 green body was sintered in a high temperature and high pressure oscillating sintering furnace. The temperature was raised to 200°C at a heating rate of 5°C / min, an oscillating pressure of 30 MPa was applied, and a current of 0.5×10 3 A; the temperature was raised from 200°C to 1200°C at a rate of 3.5°C / min, an oscillating pressure of 40 MPa was applied, and a current of 1×10 3 A; the temperature was raised from 1200℃ to 1400℃ at a rate of 1℃ / min and maintained at 1400℃ for 6h. 2×10 3 A current, during the insulation period, the oscillation pressure is reduced from 60MPa to 40MPa within 1h of the 0-1h, then the oscillation pressure is maintained at 40MPa within 1h of the 1-2h, the oscillation pressure is increased from 40MPa to 60MPa within 1h of the 2-3h, the oscillation pressure is reduced from 60MPa to 40MPa within 1h of the 3-4h, the oscillation pressure is maintained at 40MPa within 1h of the 4-5h, and the oscillation pressure is increased from 40MPa to 60MPa within 1h of the 5-6h; then the temperature is reduced from 1400℃ to 1100℃ at a rate of 1℃ / min, no oscillation pressure is applied, and no current is passed. Finally, the SrTiO3 giant dielectric ceramic material with a room temperature dielectric constant of 25578@1kHz and a dielectric loss of 0.023@1kHz is obtained.
[0056] Example 3
[0057] (1) Ingredients: Take 50g of PbTiO3 powder with a purity of 99.9%, 150g of deionized water, and 180g of zirconium oxide grinding balls = Φ10 (160g) + Φ5 (20g), and put them into two Φ250ml zirconium oxide ball mills at symmetrical positions of a planetary ball mill;
[0058] (2) Ball milling: Use a planetary ball mill with a rotation speed of 300 rpm to ball mill the PbTiO3 powder for 4 h to obtain a uniformly mixed slurry;
[0059] (3) Granulation: Add 4 wt.% polyvinyl alcohol aqueous solution to the slurry, the addition amount is 6 wt.%, and the planetary ball mill is 230 rpm. After 1.5 hours, the obtained slurry is passed through a 60-mesh screen and poured into a plastic drying basin, covered with newspaper, moved into an oven, and dried at 80°C for 48 hours. The dried powder is poured into a nylon jar with an outer specification of Φ124×15, and the zirconia grinding ball ratio is 500g=Φ20 (75g) + Φ10 (390g) + Φ5 (35g). The powder is crushed again by ball milling at a ball mill speed of 80 rpm and a ball milling time of 0.8 hours. The crushed powder is passed through a 40-mesh screen and placed in a ziplock bag;
[0060] (4) Aging: Deionized water is added to the crushed and sieved PbTiO3 powder for humidification. The amount of deionized water added is 3wt.% of the crushed and sieved PbTiO3 powder. The humidification process adopts a spraying process. After spraying, the self-sealing bag is repeatedly inverted and flipped 25 times to ensure that the water can be evenly mixed with the powder. The aging begins. The aging time is 24 hours;
[0061] (5) Dry pressing: Using a φ50 mold, the press pressure is 65 MPa, the heat preservation time is 0 min, and the mixed powder is pressed into a disc with a thickness of 5 mm;
[0062] (6) Cold isostatic pressing: The pressed discs were subjected to cold isostatic pressing at a pressure of 200 MPa and kept warm for 7 min to further improve the density of the green body. The discs were placed in air for 90 min and then dried in an oven at 100 °C to obtain PbTiO3 green bodies.
[0063] (7) Sintering: The PbTiO3 green body was sintered in a high temperature and high pressure oscillating sintering furnace. The temperature was raised to 200°C at a heating rate of 3°C / min, an oscillating pressure of 20 MPa was applied, and a current of 1×10 3 A; the temperature was raised from 200°C to 1200°C at a rate of 2.5°C / min, an oscillating pressure of 60 MPa was applied, and a current of 1.5×10 3 A; the temperature was raised from 1200℃ to 1300℃ at a rate of 1℃ / min and maintained at 1300℃ for 10h. 3×10 3A current, during the insulation period, the oscillation pressure is reduced from 60MPa to 50MPa in 1h of the 0-1h, the oscillation pressure is maintained at 50MPa in 1h of the 1-2h, the oscillation pressure is increased from 50MPa to 60MPa in 2h of the 2-4h, the oscillation pressure is reduced from 60MPa to 40MPa in 1h of the 4-5h, the oscillation pressure is maintained at 40MPa in 3h of the 5-8h, and the oscillation pressure is increased from 40MPa to 60MPa in 2h of the 8-10h, and then the temperature is reduced from 1300℃ to 1100℃ at a rate of 2℃ / min, no oscillation pressure is applied, and no current is passed. Finally, the PbTiO3 giant dielectric ceramic material with a room temperature dielectric constant of 28965@1kHz and a dielectric loss of 0.017@1kHz is obtained.
[0064] Comparative Example:
[0065] Steps (1) to (6) are the same as those in Example 1, except that:
[0066] (7) Sintering: The ceramic green body after cold isostatic pressing was sintered in a conventional silicon-molybdenum rod sintering furnace, heated to 1500°C at a heating rate of 3°C / min, and kept at 1500°C for 8 hours; cooled from 1500°C to 1100°C at a rate of 2°C / min. Finally, a BaTiO3 giant dielectric ceramic material with a room temperature dielectric constant of 18644@1kHz and a dielectric loss of 0.7@1kHz was obtained.
[0067] The difference between the comparative example and Example 1 is that the comparative example does not use a large current oscillating pressure sintering process, while Example 1 applies oscillating pressure and large current in different sintering stages. Due to the influence of the oscillating pressure, the ceramic green body is continuously squeezed during the growth of grains, the grains become smaller, and the domain walls increase; under the action of the large current, the electric domains show an oriented polarization phenomenon, and when the large current is removed, the green body can still maintain a relatively high residual polarization. Comparing the room temperature dielectric constants and dielectric losses of the two, the BaTiO3 giant dielectric ceramic material finally obtained in Example 1 of the present invention has a high dielectric constant and low dielectric loss.
[0068] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing low dielectric loss giant dielectric ceramics, characterized in that: The following steps are involved: (1) ball milling: placing the perovskite giant dielectric ceramic powder, the dispersion medium and the ball milling medium into a ball milling jar, and ball milling the perovskite giant dielectric ceramic powder at a first ball milling speed and a first ball milling time to obtain a ball milled and uniformly mixed slurry; (2) Granulation: adding polyvinyl alcohol aqueous solution to the slurry, ball milling the slurry for a second time at a second ball milling speed and a second ball milling time, drying the slurry, ball milling the slurry for a third time, and sieving the slurry to obtain a crushed powder; (3) Aging: Deionized water is added to the crushed powder to humidify it so that the water and the powder are evenly mixed, and then aging is started to obtain a mixed powder; (4) Dry pressing: using a mold and a press, at a first pressure, keeping warm for a first time, the mixed powder is pressed into a sheet of ceramic with a certain thickness; (5) Cold isostatic pressing: cold isostatic pressing is performed on the pressed ceramic disc using a second pressure and keeping the temperature for a second time, and the disc is placed in the air to stand for a while and then dried; (6) Sintering: The cold isostatically pressed ceramic sheets are moved into an oscillating sintering furnace and a high current oscillating pressure sintering process is used. Oscillating pressure and high current are applied in different sintering stages. After cooling, a perovskite-type giant dielectric ceramic with a high dielectric constant and low dielectric loss is obtained.
2. The preparation method according to claim 1, characterized in that: The perovskite-based giant dielectric ceramic powder includes BaTiO3 powder, PbTiO3 powder or SrTiO3 powder; the purity of the perovskite-based giant dielectric ceramic powder is ≥99.9%.
3. The preparation method according to claim 1, characterized in that: The dispersion medium is deionized water, the ball milling medium is a zirconia grinding ball with an addition ratio of φ10:φ5=(8-4):1; the ball milling jar is a nylon material or a zirconia material of 250nm-500ml; the ball mill is a vertical planetary ball mill, the first ball milling speed is 300rpm-400rpm, and the first ball milling time is 2-4h; the weight ratio of the perovskite giant dielectric ceramic powder to the ball milling medium is 1:(2-5); the weight ratio of the perovskite giant dielectric ceramic powder to deionized water is 1:(2-3).
4. The preparation method according to claim 1, characterized in that: The concentration of the polyvinyl alcohol aqueous solution is 3wt.%-5wt.%, the mass percentage of the added polyvinyl alcohol aqueous solution to the slurry is 5wt.%-8wt.%, the second ball milling speed is 200-250rpm, and the second ball milling time is 1-2h.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The slurry after the second ball milling is passed through a 20-80 mesh sieve, then moved into an oven and dried at 60°C-100°C for 24h-48h. The dried powder is poured into a nylon jar and milled for the third time at a ball mill speed of 60rpm-100rpm and a ball milling time of 0.5h-1h according to the ratio of zirconia grinding balls 500g=Φ20 (75g) + Φ10 (390g) + Φ5 (35g). The crushed powder is then passed through a 20-100 mesh sieve and put into a ziplock bag.
6. The preparation method according to claim 5, characterized in that: The aging includes spraying deionized water into the crushed and sieved powder for humidification at a ratio of 1-3wt.% of deionized water to the crushed powder, repeatedly inverting and flipping the ziplock bag after spraying, the number of inversions and flippings is not less than 20 times, so that the water can be evenly mixed with the powder, and then aging for not less than 24 hours.
7. The preparation method according to claim 6, characterized in that: The first pressure is 60-75 MPa, and the first insulation time is 0-1 min; the second pressure is 200-250 MPa, and the second insulation time is 3-7 min; the wafer is placed in the air for 50-90 min, and then placed in a 60°C-100°C oven for drying.
8. The preparation method according to claim 7, characterized in that: The sintering stage includes: Heating to 200°C at a heating rate of 1-5°C / min; Raise the temperature from 200°C to 1200°C at a rate of 0.5-3.5°C / min; The temperature was raised from 1200℃ to T at a rate of 0.2-1℃ / min. max , and at T max Keep at ℃ for 6-10h; At a rate of 0.5-3.5℃ / min, the temperature max Cool down to 1100℃.
9. The preparation method according to claim 8, characterized in that: The high current oscillating pressure sintering process comprises the following steps: The temperature was raised to 200°C at a rate of 1-5°C / min, an oscillating pressure of 10-30MPa was applied, and a current of (0.5-1)×10 3 A; The temperature was raised from 200°C to 1200°C at a rate of 0.5-3.5°C / min, an oscillating pressure of 30-60MPa was applied, and a current of (1-2)×10 3 A; The temperature is raised from 1200°C to T at a rate of 0.2-1°C / min. max , and at T max ℃ for 6-10h, apply an oscillating pressure of 40-60MPa, and pass a current of (2-4)×10 3 A; The rate of 0.5-3.5°C / min is increased from T max Cool down to 1100°C, without applying oscillating pressure or passing current; The T max It is 1300℃-1500℃.
10. A low dielectric loss giant dielectric ceramic, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of giant-dielectric-constant barium titanate ceramic
CN103214237B
In + Ta co-doped TiO2-based giant dielectric ceramic as well as preparation method and application thereof
CN114262223A
Giant dielectric constant and low dielectric loss CCTO ceramic material and preparation method thereof
CN115321976A
Ti-position high-valence substituted SrTiO3 giant dielectric ceramic and preparation method thereof
CN105130421A
Dielectric ceramic material with giant dielectric constant and low dielectric loss and method for preparing dielectric ceramic material
CN105777111A